Anomalous localization of light in one-dimensional disordered photonic superlattices (2013)
ABSTRACT: The Anderson localization of light in one-dimensional disordered photonic superlattices is theoretically studied. The system is considered to be made of alternating dispersive and nondispersive layers of different randomthickness. Dispersive slabs of the heterostructure are characterized by Drude-like frequency-dependent electric permittivities and magnetic permeabilities. Numerical results for the localization length are obtained via an analytical model, only valid in the case of weak disorder, and also through its general definition involving the transmissivity of the multilayered system. Anomalous λ 4 - and λ−4 dependencies of the localization length in positive-negative disordered photonic superlattices are obtained, in certain cases, in the long and short wavelength limits, respectively.